Anion-regulated weak-solvation sulfuryl electrolyte and preparation method thereof
By adding high-donor lithium salts and common lithium salts to the sulfone-based electrolyte, a weak solvation structure is constructed, which solves the compatibility and cycle performance problems of the sulfone-based electrolyte under high voltage and wide temperature ranges, and realizes lithium-ion Efficient and safe electrochemical performance of batteries.
Patent Information
- Application Number
- CN202411765590.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing sulfone-based electrolytes exhibit high viscosity, poor wetting and poor compatibility under high voltage and wide temperature ranges, which affects the circulation performance and safety of lithium-ion batteries.
The weak solvents regulated by the anionic ions are used to build a weak solvent -based structure by adding high -donor lithium salt and common lithium salt to the electrolyte to improve the combination capacity of lithium ions and the solubility of electrolytes.
The stable operation of lithium -ion batteries in high voltage and wide temperature range, improved the cycle performance and safety of the battery, and reduced the preparation cost of the electrolyte.
Smart Images

Figure CN119361837A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery electrolytes, and in particular relates to an anion-regulated weakly solvated sulfone-based electrolyte and a preparation method thereof. Background Art
[0002] Compared with traditional carbonate-based electrolyte systems, sulfone solvents are considered to be potential high-voltage electrolyte solvents due to their low price and high oxidation stability. However, sulfone solvents have poor compatibility with lithium metal and graphite anodes, and their high melting point, high viscosity and low wettability greatly reduce their practicality.
[0003] At present, researchers usually use high-concentration electrolytes (HCEs) or local high-concentration electrolytes (LHCEs) to adjust the solvation structure of sulfone-based electrolytes to improve the electrochemical performance of lithium-ion batteries. For example, by increasing the concentration of lithium hexafluorophosphate (LiPF6) salt in the electrolyte, an inorganic-rich solid electrolyte interface (SEI) film is formed, thereby improving the battery's cycling performance. However, higher salt concentrations lead to higher viscosity and poorer wettability of sulfone-based electrolytes, hindering ion transport and thus affecting battery cycling performance. Although the introduction of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) as a diluent solves the problem of high viscosity of HCEs, most of the reported diluents are fluorinated ethers, which have low boiling points and volatilization problems, limiting the use of sulfone-based electrolytes at high temperatures. In addition, the addition of diluents increases the cost and complexity of the electrolyte. Therefore, the development of a new sulfone-based electrolyte with high efficiency, simplicity and economy is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present invention aims at solving the problems in the prior art and provides a lithium ion battery sulfone-based electrolyte having high voltage resistance, wide temperature range, high cycle life and high safety performance.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0006] A weakly solvated sulfone-based electrolyte regulated by anions, characterized in that it comprises: a high-donor lithium salt, a sulfone solvent and a common lithium salt.
[0007] Furthermore, the high donor lithium salt includes one or more of lithium nitrate, lithium trifluoromethanesulfonate and lithium bromide.
[0008] Furthermore, the sulfone solvent includes one or more of sulfolane, dimethyl sulfoxide, dimethyl sulfone, dibutyl sulfone, dipropyl sulfone, diethyl sulfone, benzyl sulfone, diphenyl sulfone, ethyl methyl sulfone, ethyl phenyl sulfone, phenylmethyl sulfone, methoxyethyl methyl sulfone, ethyl methoxyethyl sulfone, and ethyl methoxyethoxyethyl sulfone.
[0009] Furthermore, the common lithium salts include one or more of lithium difluorooxalatoborate (LiDFOB), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(oxalatoborate) (LiBOB), lithium bis(difluorosulfonylimide) (LiFSI), lithium bis(trifluoromethylsulfonylimide) (LiTFSI) and lithium hexafluorophosphate (LiPF6).
[0010] The high-donor lithium salt, sulfone solvent and common lithium salt used in the present invention are all commercially available.
[0011] Furthermore, the concentrations of the high donor lithium salt and the common lithium salt are less than 1 mol / L, and the molar ratio of the high donor lithium salt to the common lithium salt is (1-5):(5-1).
[0012] Furthermore, the electrolyte is applicable to a wide temperature range and can operate stably in an environment of -40°C to 80°C; the electrolyte can maintain excellent performance under high voltage (4.4V).
[0013] A method for preparing an anion-regulated weakly solvated sulfone-based electrolyte comprises the following steps: dissolving a common lithium salt in a sulfone solvent, adding a high-donor lithium salt, and mixing and stirring until uniform.
[0014] A lithium ion battery comprises the anion-regulated weakly solvated sulfone-based electrolyte of the present invention.
[0015] Furthermore, the lithium-ion battery also includes a positive electrode material and a negative electrode material.
[0016] Furthermore, the positive electrode material includes any one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium-rich material, nickel-cobalt-manganese ternary material and nickel-cobalt-aluminum ternary material; the negative electrode material includes any one of lithium metal, graphite, lithium titanate, silicon, silicon carbon and hard carbon.
[0017] The high donor number anion added by the present invention can strongly bind to the lithium ion, and its binding ability is greater than the binding force between the lithium ion and the sulfone solvent, and has good solubility in the sulfone-based solution. For example: by using the nitrate ion of the high donor number lithium salt LiNO3, the coordination structure between the lithium ion and the sulfone solvent (such as cyclopentane (SL)) is effectively weakened, and the interaction between the lithium ion and the difluorooxy oxalate borate ion is enhanced. By constructing the weak solvation structure above, the new solvation structure not only promotes the lithium ion desolvation process, but also promotes the decomposition of common lithium salts. At the same time, the high donor lithium salt is oxidized and reduced on the electrode surface to form a solid electrolyte interface (SEI) layer rich in inorganic substances, which further improves the interface stability between SL and lithium metal, and is conducive to ion transmission, promotes the deposition and stripping of lithium, solves the problem of poor compatibility of sulfone solvents with lithium metal and graphite negative electrodes, and improves the cycle performance, high and low temperature resistance, and high voltage resistance of the weakly solvated sulfone-based electrolyte battery.
[0018] Beneficial Effects
[0019] The present invention provides a sulfone-based lithium-ion battery electrolyte with low salt concentration, high voltage resistance, and stable operation in a wide temperature range. By constructing a weak solvation structure, the compatibility of the sulfone-based electrolyte with lithium metal is improved, the growth of lithium dendrites and the decomposition of the electrolyte are effectively inhibited, and the cycle performance of the lithium-ion battery is improved. At the same time, the electrolyte has excellent antioxidant properties. In addition, the electrolyte can still operate stably in a wide temperature range (-40°C to 80°C) and is suitable for more application scenarios. The present invention reduces the preparation cost of the electrolyte and improves its commercial feasibility through a simple preparation process and low-cost raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 For Li + With SL, DFOB - and NO 3- Binding energy test diagram;
[0021] Figure 2 These are the Raman test images of Example 1 and Comparative Example 1;
[0022] Figure 3 This is a diagram for verifying the weak solvation structure of Example 1;
[0023] Figure 4 This is an X-ray photoelectron spectroscopy (XPS) test diagram of the lithium metal side in Example 1;
[0024] Figure 5 X-ray photoelectron spectroscopy (XPS) test image of the positive electrode side of lithium cobalt oxide;
[0025] Figure 6 For comparative examples 1-3 ( Figure 6 a, 6b, 6c), Example 1 ( Figure 6 d) A button cell consisting of a lithium sheet and a copper sheet at 4 mA cm -2 After lithium was deposited at a current density of for 4 hours, the lithium deposition morphology was observed using a scanning electron microscope;
[0026] Figure 7 This is a long cycle performance diagram of lithium / lithium cobalt oxide batteries using Examples 1, 2, 3, 4 and 5 at 25°C;
[0027] Figure 8 This is a long cycle performance diagram of the lithium / lithium cobalt oxide battery of Example 6-18 at 25°C;
[0028] Fig. 9 This is a long cycle performance diagram of the lithium / lithium cobalt oxide battery of Comparative Examples 1, 2, and 3 at 25°C;
[0029] Fig.10 The cycle performance diagram and charge-discharge curve diagram of the lithium / lithium cobalt oxide battery of Example 1 at 80°C;
[0030] Fig.11 The cycle performance diagram and charge-discharge curve diagram of the lithium / lithium cobalt oxide battery of Example 1 at -40°C;
[0031] Fig.12 The figure is a cycle performance diagram and a charge and discharge curve diagram of the lithium / graphite battery of Example 1 at 25°C. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0033] Example 1
[0034] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiDFOB and 0.2 M LiNO3 were added to sulfolane to prepare SL-0.2 M LiNO3-0.5 M LiDFOB electrolyte.
[0035] Example 2
[0036] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.3 M LiDFOB and 0.5 M LiNO3 were added to sulfolane to prepare SL-0.3 M LiNO3-0.5 M LiDFOB electrolyte.
[0037] Example 3
[0038] In an argon glove box with water and oxygen contents less than 0.1 ppm, 1 M LiDFOB and 0.2 M LiNO3 were added to sulfolane to prepare SL-0.2 M LiNO3-1 M LiDFOB electrolyte.
[0039] Example 4
[0040] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.2 M LiDFOB and 0.2 M LiNO3 were added to sulfolane to prepare SL-0.2 M LiNO3-0.2 M LiDFOB electrolyte.
[0041] Example 5
[0042] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.1 M LiDFOB and 0.5 M LiNO3 were added to sulfolane to prepare SL-0.1 M LiNO3-0.5 M LiDFOB electrolyte.
[0043] Example 6
[0044] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiTFSI and 0.2 M LiNO3 were added to dimethyl sulfone (DS) to prepare DS-0.2 M LiNO3-0.5 M LiTFSI electrolyte.
[0045] Example 7
[0046] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiBOB and 0.2 M LiNO 3 were added to dibutyl sulfone (DBS) to prepare DBS-0.2 M LiNO 3 -0.5 M LiBOB electrolyte.
[0047] Example 8
[0048] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiClO4 and 0.2 M LiTf were added to dipropyl sulfone (DPS) to prepare DPS-0.2 M LiTf-0.5 LiClO4 electrolyte.
[0049] Example 9
[0050] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiTFSI and 0.2 M LiBr were added to diethyl sulfone (DES) to prepare DES-0.5 M LiBF4-0.2 M LiBr electrolyte.
[0051] Example 10
[0052] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiBF4 and 0.2 M LiBr were added to benzyl sulfone (BMS) to prepare BMS-0.5 M LiBF4-0.2 M LiBr electrolyte.
[0053] Embodiment 11
[0054] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiBOB and 0.2 M LiNO3 were added to dimethyl sulfoxide (DMSO) to prepare DMSO-0.2 M LiNO3-0.5 M LiPF6 electrolyte.
[0055] Example 12
[0056] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiFSI and 0.2 M LiTf were added to diphenyl sulfone (DPSO) to prepare DPSO-0.2 M LiTf-0.5 M LiFSI electrolyte.
[0057] Embodiment 13
[0058] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiAsF6 and 0.2 M LiBr were added to ethyl methyl sulfone (EMSO) to prepare EMSO-0.2 M LiBr-0.5 M LiAsF6 electrolyte.
[0059] Embodiment 14
[0060] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiAsF6 and 0.2 M LiBr were added to ethyl phenyl sulfone (EPSO) to prepare EPSO-0.2 M LiBr-0.5 M LiAsF6 electrolyte.
[0061] Embodiment 15
[0062] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiAsF6 and 0.2 M LiBr were added to benzyl sulfone (BAS) to prepare BAS-0.2 M LiBr-0.5 M LiAsF6 electrolyte.
[0063] Example 16
[0064] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiAsF6 and 0.2 M LiBr were added to methoxyethyl methyl sulfone (MEMS) to prepare MEMS-0.2 M LiBr-0.5 M LiAsF6 electrolyte.
[0065] Embodiment 17
[0066] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiAsF6 and 0.2 M LiBr were added to ethyl methoxyethyl sulfone (EEMS) to prepare EEMS-0.2 M LiBr-0.5 M LiAsF6 electrolyte.
[0067] Embodiment 18
[0068] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiAsF6 and 0.2 M LiBr were added to ethyl methoxyethoxyethyl sulfone (EBOES) to prepare EBOES-0.2 M LiBr-0.5 M LiAsF6 electrolyte.
[0069] Comparative Example 1
[0070] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.5 M LiDFOB was added to SL to prepare the SL-LiDFOB electrolyte.
[0071] Comparative Example 2
[0072] In an argon glove box with water and oxygen contents less than 0.1 ppm, 0.2 M LiNO3 was added to SL to prepare the SL-LiNO3 electrolyte.
[0073] Comparative Example 3
[0074] In an argon glove box with water and oxygen contents less than 0.1 ppm, the electrolyte was prepared: 1M LiPF6 was dissolved in ethylene carbonate (EC) and dimethyl carbonate (DMC) solvent with a volume ratio of 1:1 (EC / DMC (v:v=1:1)) to prepare EC / DMC-LiPF6 electrolyte.
[0075] Performance Testing
[0076] Conduct various data tests on the electrolyte
[0077] (1) Opposition + With SL, DFOB - and NO 3- The binding energy was determined
[0078] Gaussian16 software was used for DFT calculations. All DFT calculations were performed at the B3LYP / 6-3111+G(d, p) level. First, the cluster model required for the calculation was constructed with the help of Gass View. Then, the structures of all clusters were optimized at the corresponding calculation level. Finally, the anions and cations in the clusters were extracted and the Li + With DFOB- /
[0079] NO 3- / binding energy between sulfonated alkanes.
[0080] like Figure 1 As shown, DFT theoretical calculation of Li + With SL, DFOB - and NO3 - Binding energy of NO3 - With Li + The interaction energy of NO is higher than that of Li-SL. 3- When introduced, NO 3- Compete with SL to weaken Li + The coordination effect between Li + With DFOB - Therefore, after adding high donor number lithium salt LiNO3, Li + As the concentration of DFOB increases, - Can be with more Li + coordination, which provides a basis for constructing anion-enhanced weakly solvated structures.
[0081] (2) Raman testing of TF and TFN electrolytes
[0082] TFN is 0.5M LiDFOB-0.2M LiNO3-SL (Example 1), TF is 0.5M LiDFOB-SL (Comparative Example 1), the laser is turned on for preheating for half an hour, the test sample is placed in a glass bottle, and the sample is kept in a dark environment for testing. The Raman instrument model is HORIBA JY LabRAM HR Evolution.
[0083] like Figure 2 a, 1025cm -1 The peak and NO 3- In TFN electrolyte, the peak position shifts to high frequency, indicating that free NO3 - The decrease in NO3 - Participates in the solvation sheath.
[0084] like Figure 2 As shown in b, the stretching vibration peak of CSC in sulfolane increases from 745 cm -1 Red shift to 735cm -1 , indicating that SL and Li + The interaction is weakened in TFN electrolyte.
[0085] like Figure 2 c, at 1735-1885cm-1 Corresponding to DFOB - In the TFN electrolyte, the significant increase in contact ions (CIPs) indicates that Li + With DFOB - The coordination is enhanced.
[0086] (3) Example 1 Weak Solvation Structure Verification
[0087] TFN (Example 1) and TF (Comparative Example 1) electrolytes were prepared for NMR. 7Li NMR spectra were recorded using a 600M NMR JNM-ECZ600R / S1 system. D2O (1.0 mol L -1 ) is an external reference, which is set to 0 ppm. During the entire experiment, the operating environment was ensured to be dry and free of moisture to reduce the impact on the sample.
[0088] like Figure 3 As shown, add NO 3- , TFN all move to the low field, verifying the weak solvation structure of TFN electrolyte. (4) Universal force field (UFF) and RESP partial charge description of TFN (Example 1) and TF (Comparative Example 1) electrolyte molecular structure
[0089] The simulation model was constructed using the Packmol package. First, the model was energy minimized. Then, molecular dynamics calculations were performed on the model at a temperature of 298 K and a pressure of 1 atm in the NPT ensemble. The total molecular dynamics simulation time was 500 ps, of which the first 300 ps was used for structural relaxation and the last 200 ps was used for subsequent data analysis. For the calculated trajectory files, the VMD software package was used to calculate the radial distribution functions of the corresponding Li-O / Li-F atomic pairs in the system, and the corresponding average coordination numbers were calculated and shown in Table 1.
[0090] Table 1 Average coordination number
[0091] Coordination number Li-O(SL) Li-O(DFOB) <![CDATA[Li-O(NO3)]]> TF 3.960 0.039 - TFN 3.754 0.046 0.198
[0092] As shown in the table above, the coordination number of Li-O(SL) in TF electrolyte is 3.960. 3- After , the coordination number decreased to 3.754, while the coordination number of Li-O(DFOB) increased from 0.039 to 0.046. This indicates that NO 3- The introduction of formed a unique anion-enhanced weak solvation structure.
[0093] (5) X-ray photoelectron spectroscopy (XPS) test on the lithium metal side
[0094] The electrolyte used was TFN (Example 1). After 100 cycles, the lithium sheet was removed from the Li / LCO battery, and the surface of the lithium sheet was rinsed with DMC solvent. A clean tool was used to cut the lithium metal side into sample pieces of appropriate size to ensure that the surface was flat. To avoid contamination of the lithium metal surface, the entire process was operated under argon. The cut lithium metal sample was placed in the XPS vacuum chamber, and the sample was scanned to record the characteristic peaks of the Li element.
[0095] After the Li / LCO battery is cycled 100 times, the X-ray photoelectron spectroscopy (XPS) on the lithium metal side is as follows Figure 4 As shown, after the TFN electrolyte cycles, LiF and LiNxOy protective layers are formed on the surface of lithium metal.
[0096] (6) X-ray photoelectron spectroscopy (XPS) test on the positive electrode side of lithium cobalt oxide
[0097] The electrolyte used was TFN (Example 1). After 100 cycles, the lithium cobalt oxide positive electrode sheet was disassembled from the Li / LCO battery. The positive electrode surface was rinsed with DMC solvent, and the lithium metal side was cut into sample pieces of appropriate size using a clean tool. To avoid contamination of the lithium metal surface, the entire process was operated under argon. The cut positive electrode sheet sample was placed in the XPS vacuum chamber, and the sample was scanned to record the characteristic peak of the F element.
[0098] After the Li / LCO battery is cycled 100 times, the X-ray photoelectron spectroscopy (XPS) of the lithium cobalt oxide positive electrode side is as follows Figure 5 As shown, after circulating in the TFN electrolyte, a LiF protective layer is formed on the surface of the lithium cobalt oxide positive electrode.
[0099] The electrolyte prepared by the present invention is used to prepare a lithium ion battery, and the electrochemical performance test is performed.
[0100] 1. Preparation of Electrolyte
[0101] The electrolyte was prepared by the preparation method of Example 1.
[0102] 2. Preparation of positive electrode
[0103] The lithium cobalt oxide positive electrode material, super conductive agent (Super P) and polyvinylidene fluoride (PVDF) binder are uniformly dispersed in a certain amount of N-methylpyrrolidone (NMP) solvent according to a mass ratio of 8:1:1, coated on aluminum foil, dried, and rolled to prepare the positive electrode. The positive electrode loading is 10 mg / cm 2 .
[0104] 3. Preparation of graphite anode
[0105] The graphite negative electrode material was mixed with conductive carbon black (Super P), thickener (CMC) and polyvinylidene fluoride (SBR) binder in a mass ratio of 93:2:2.5:2.5 to form a slurry, which was coated on a copper foil, dried and rolled to prepare a graphite negative electrode.
[0106] 4. Battery Preparation
[0107] In an argon glove box with water and oxygen content less than 0.1 ppm, the following order is used for assembly: negative electrode shell / lithium sheet / electrolyte / diaphragm / electrolyte / steel sheet / shrapnel / positive electrode shell. After sealing and pressing, the button battery is assembled.
[0108] 5. Material battery performance test
[0109] Battery cycle test: At 25°C, the battery was charged and discharged for 2 cycles at a current density of 0.1C (1C = 160mAh / g), with a charge cut-off potential of 4.4V and a discharge cut-off potential of 3V. After activation, the battery was subjected to a cycle performance test.
[0110] Battery cycle test: The battery is charged to 4.4V at 0.5C constant current at 25℃, and discharged to 3V at 0.5C; constant current charge and discharge are performed twice at 80℃ and -40℃ for cycle test.
[0111] Characterization of lithium deposition morphology: 4 mA cm -2 Lithium was deposited on copper foil at a current density of for 4 hours, and then the deposition morphology of lithium was observed using a scanning electron microscope.
[0112] Figure 6 It is a button cell battery composed of lithium and copper sheets. -2 Lithium was deposited at a current density of 4 h, and the lithium deposition morphology was observed by scanning electron microscopy. The results show that in Comparative Examples 1, 2, and 3, the metallic lithium exhibited high porosity and dendrites ( Figure 6 In contrast, in Example 1, the metallic lithium is densely packed ( Figure 6 d) This shows that Example 1 has good compatibility with lithium metal, which is of great significance to the long cycle of the battery.
[0113] Figure 7 Respectively, Example 1 ( Figure 7 a), Example 2 ( Figure 7 b) Example 3 Figure 7 c) Example 4 ( Figure 7 d), Example 5 ( Figure 7e) Long cycle performance diagram of lithium / lithium cobalt oxide battery with electrolyte at 25°C. The results show that the battery using Example 1 has the highest discharge specific capacity and the slowest capacity decay. After 1000 cycles, the capacity retention rate is as high as 93.3%, indicating that the addition of 0.2M LiNO3 and 0.5M LiDFOB is the best ratio.
[0114] Figure 8 The long cycle diagram of the lithium / lithium cobalt oxide battery using Examples 6-18 at 25°C. The results show that different sulfone-based electrolytes adjusted by high-donor number lithium salts can significantly improve the cycle life of the battery and greatly reduce the capacity decay rate, which illustrates the universality of this work.
[0115] Fig. 9 Comparative Example 1 ( Fig. 9 a), Comparative Example 2 ( Fig. 9 b) and Comparative Example 3 ( Fig. 9 c) Long cycle performance diagram of lithium / lithium cobalt oxide battery with electrolyte at 25°C. The results show that the capacity decay rate of the batteries using comparative examples 1, 2, and 3 is greater than that of the battery using example 1, which indicates that the sulfone-based electrolyte with anion-regulated weak solvation has the feasibility of practical application.
[0116] Fig.10 The long cycle performance of the lithium / lithium cobalt oxide battery using the electrolyte of Example 1 at 80° C. It can be seen that the battery capacity decay is small, indicating that the battery using Example 1 can be applied to 80° C.
[0117] Fig.11 The long cycle performance of the lithium / lithium cobalt oxide battery using the electrolyte of Example 1 at -40°C. It can be seen that the battery charge and discharge curve is stable, indicating that the battery using Example 1 can be applied to -40°C.
[0118] Fig.12 This is the long cycle performance of the lithium / graphite battery of Example 1. It can be seen that the battery charge and discharge curve is stable, indicating that this work solves the problem of incompatibility between sulfolane and graphite negative electrode.
[0119] In summary, the present invention provides an anion-regulated weakly solvated sulfone-based electrolyte and a preparation method thereof, wherein a high-donor lithium salt and a common lithium salt are added to a sulfone compound in different molar ratios to form an electrolyte. The electrolyte is a sulfone-based lithium ion battery electrolyte that is resistant to high voltage and operates stably over a wide temperature range. By constructing a weakly solvated structure, the compatibility of the sulfone-based electrolyte with lithium metal is improved, the growth of lithium dendrites and the decomposition of the electrolyte are effectively inhibited, and the cycle performance of the lithium ion battery is improved.
[0120] It should be noted that the above embodiments are only some embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A weakly solvated sulfone-based electrolyte regulated by anions, characterized in that: Including high donor lithium salts, sulfone solvents and common lithium salts.
2. The anion-regulated weakly solvated sulfone-based electrolyte according to claim 1, characterized in that: The high donor lithium salt is one or more of lithium nitrate, lithium trifluoromethanesulfonate and lithium bromide.
3. The anion-regulated weakly solvated sulfone-based electrolyte according to claim 1, characterized in that: The sulfone solvent includes one or more of sulfolane, dimethyl sulfoxide, dimethyl sulfone, dibutyl sulfone, dipropyl sulfone, diethyl sulfone, benzyl sulfone, diphenyl sulfone, ethyl methyl sulfone, ethyl phenyl sulfone, phenylmethyl sulfone, methoxyethyl methyl sulfone, ethyl methoxyethyl sulfone, and ethyl methoxyethoxyethyl sulfone.
4. The anion-regulated weakly solvated sulfone-based electrolyte according to claim 1, characterized in that: The common lithium salt is one or more of lithium difluorooxalatoborate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium bis(difluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide) and lithium hexafluorophosphate.
5. The anion-regulated weakly solvated sulfone-based electrolyte according to claim 1, characterized in that: The concentrations of the high donor lithium salt and the common lithium salt are less than or equal to 1 mol / L, and the molar ratio of the high donor lithium salt to the common lithium salt is (1-5):(5-1).
6. The anion-regulated weakly solvated sulfone-based electrolyte according to claim 1, characterized in that: The electrolyte is suitable for temperatures ranging from -40°C to 80°C.
7. A method for preparing the anion-regulated weakly solvated sulfone-based electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: In an argon glove box with water and oxygen contents less than 0.1 ppm, a common lithium salt is dissolved in a sulfone solvent, and then a high-donor lithium salt is added, and the mixture is stirred until uniform to obtain a weakly solvated sulfone-based electrolyte.
Citation Information
Patent Citations
Electrolyte based on sulfuryl eutectic solvent, preparation method of electrolyte and lithium ion battery
CN115458811A
Wide-temperature-range fast-charging mixed salt electrolyte and preparation method thereof
CN118156617A
Wide-temperature, high-voltage and high-ionic-conductivity lithium battery electrolyte
CN118610584A
Organic electrolyte battery
JP2000048859A
Electrolyte with high lifsi concentration
WO2024241002A1
Cited By
Wide-temperature high-voltage sulfuryl electrolyte and preparation method thereof
CN120933483A
Wide-temperature high-voltage sulfone-based electrolyte and preparation method thereof
CN120933483B
Electrolyte, preparation method thereof and lithium ion battery
CN121529012A